2008
DOI: 10.1038/nsmb.1411
|View full text |Cite
|
Sign up to set email alerts
|

The exonuclease ERI-1 has a conserved dual role in 5.8S rRNA processing and RNAi

Abstract: The exonuclease ERI-1 negatively regulates RNA interference (RNAi) in Caenorhabiditis elegans and Schizosaccharomyces pombe, and is required for production of some C. elegans endogenous small-interfering RNAs. We show that ERI-1 performs 3′ end processing of the 5.8S ribosomal RNA (rRNA) in both C. elegans and S. pombe. In C. elegans, two protein isoforms of ERI-1 are localized to the cytoplasm, and each has distinct functions in rRNA processing and negative regulation of RNAi.The C. elegans eri-1 gene encode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
69
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 14 publications
2
69
0
4
Order By: Relevance
“…Eri1 associates with ribosomes and binds to rRNA precursors and 5.8S rRNA in cells. The appearance of a 3′-extended 5.8S rRNA in C. elegans eri-1 mutants indicates that ERI-1 is required for 5.8S rRNA processing 10 , and our observation of a similar defect in Eri1-deficient mice demonstrates that this is a conserved feature of Eri1 function. Reconstitution experiments in Eri1-deficient cells and in vitro processing reactions with recombinant Eri1 revealed that Eri1 exonuclease activity is necessary and sufficient to catalyze the final step in 5.8S rRNA 3′ end formation.…”
supporting
confidence: 63%
See 4 more Smart Citations
“…Eri1 associates with ribosomes and binds to rRNA precursors and 5.8S rRNA in cells. The appearance of a 3′-extended 5.8S rRNA in C. elegans eri-1 mutants indicates that ERI-1 is required for 5.8S rRNA processing 10 , and our observation of a similar defect in Eri1-deficient mice demonstrates that this is a conserved feature of Eri1 function. Reconstitution experiments in Eri1-deficient cells and in vitro processing reactions with recombinant Eri1 revealed that Eri1 exonuclease activity is necessary and sufficient to catalyze the final step in 5.8S rRNA 3′ end formation.…”
supporting
confidence: 63%
“…Yet our understanding of ribosome biogenesis remains incomplete. In the accompanying manuscript, Gabel and Ruvkun demonstrate that eri-1 is essential for the maturation of the 3′ end of 5.8S rRNA in fission yeast and nematodes 10 . Together with our findings in mice, these results establish Eri1 as a conserved component of the rRNA processing machinery from fission yeast to mice.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations